Numerical Average-Value Modeling of Rotating Rectifiers in Brushless Excitation Systems - YuQi Zhang; Cramer, Aaron M. (IEEE transactions on energy conversion, 2017)
Brushless excitation systems are widely used for synchronous machines. As a critical part of the system, rotating rectifiers have a significant impact on the system behavior. This paper presents a numerical average-value model (AVM) for rotating rectifiers in brushless excitation systems, where the essential numerical functions are extracted from the detailed simulations and vary depending on the loading conditions. Open-circuit voltages of the brushless exciter armature are used to calculate the dynamic impedance that represents the loading condition. The model is validated by comparison with an experimentally validated detailed model of the brushless excitation system in three distinct cases. It has been demonstrated that the proposed AVM can provide accurate simulations in both transient and steady states with fewer time steps and less runtime compared with detailed models of such systems and that the proposed AVM can be combined with AVM models of other rectifiers in the system to reduce the overall computational cost.